The role of geography teachers in enhancing earthquake and tsunami disaster preparedness among students in Banda Aceh - Abdul Wahab Abdi; Mirza Desfandi; Sigorina Kasvia (Jurnal Sosioteknologi, 2020)
This study is aimed to find out the role of geography teachers in enhancing earthquake and tsunami disaster preparedness among students of Senior High School in Banda Aceh. This study is descriptive study by using quantitative approach. This study was conducted in eight Senior High Schools in Banda Aceh with study samples were 15 geography teachers and 10 students in each school who were selected by Purposive Random Sampling. Data collection technique was done through questionnaire distributed to teachers and test items to students. Data analysis technique used descriptive statistic. The study result showed that teacher's role in enhancing earthquake and tsunami disaster preparedness among students is dominated by medium category (40%). Based on this study result, it can be concluded that the role of geography teachers in enhancing students' preparedness is not satisfying.